APLIKASI PERENCANAAN PEMBELIAN BARANG PADA PERUSAHAAN MANGGALA MOTOR DENGAN MENGGUNAKAN METODE ARIMA - ., Yulia; Octavia, Tanti; Wijaya, Danny (Institute of Research and Community Outreach - Petra Christian University, 2009)
Manggala Motor is a vehicles selling company. Occasionally the company lacks goods stock so that it can not obtain maximal profit because the customer needs can not be compiled by the company directly. The company needs an application that can forecast the motorcycles selling for next period, the application is expected to solve the company’s problem. The application is made by using ARIMA method (Autoregressive-Integrated-Moving Average). The result of this application is information about the selling forecasting in the next period. It is hoped that the selling forecasting can help the company to prepare the goods stock and fulfill the costumers demand.